(untitled) (Tamaddun, 2024)
This study investigates the challenges faced by fifth-semester English Department students at the Muslim University of Indonesia in achieving effective English proficiency. It is a qualitative descriptive research approach. Data were collected from five participants through observations, semi-structured interviews, and documentation, enabling an in-depth exploration of cognitive, affective, and environmental factors. The findings highlight six principal obstacles: insufficient practice, limited vocabulary, unsupportive learning environments, lack of interest, low self-confidence, and difficulties with pronunciation. Additionally, participants reported five key coping strategies, including regular vocabulary expansion, consistent practice, seeking training partners, enhancing learning motivation, and developing self-confidence. These strategies underscore the importance of addressing both linguistic and psychological dimensions of language acquisition. The results align with prominent theories in second language acquisition, emphasizing the role of socially mediated interactions, motivation, and affective factors. Practically, the study suggests implementing collaborative learning approaches, structured practice sessions, and confidence-building activities in English language curricula to foster communicative competence. Although this investigation focuses on a single private university context and has a limited sample size, its insights hold relevance for educators, policymakers, and institutions seeking to improve English language instruction. Future research could investigate broader populations, alternative instructional settings, and longitudinal assessments of student progress. Therefore, the study contributes valuable perspectives on how to overcome persistent English language difficulties among university students in similar EFL settings.